Case Report: Furmonertinib-induced acute interstitial lung disease - Niu, Yong-liang; Yang, Ying; Shi, Jing-feng; Han, Ming-feng; Wang, Di-ming (Frontiers in Pharmacology, 2026)
Furmonertinib is a third-generation irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) that selectively inhibits EGFR-TKI-sensitive mutations. Although furmonertinib is generally well-tolerated and no severe drug-related interstitial lung disease (ILD) has been reported in the literature to date, we present a case of furmonertinib-induced ILD in a 71-year-old woman with EGFR-mutated lung adenocarcinoma (LUAD). On day 97 of treatment, the patient developed acute severe dyspnea, which rapidly progressed to diffuse bilateral lung consolidation and profound hypoxemia. After excluding other potential causes of interstitial pneumonia, a diagnosis of furmonertinib-related ILD was established. Through timely diagnosis and appropriate intervention, the patient achieved a favorable outcome. This case highlights that early recognition and management can reverse this serious adverse event and help preserve subsequent treatment options.